Why Polish apples are present on the Romanian markets? - Marius Mihai Micu; Valentina Constanța Tudor; Dragoș Ion Smedescu; Cosmina Andreea Carbarău (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
With millions of tons harvested annually, the apple is the third fruit consumed in the world, after oranges and bananas. In 1989, Romania had 79,000 ha of apple trees, but in 2017 the situation was different, with about 55,000 ha planted, occupying the second place in the EU after Poland, the leader of the apple cultivated area and production. The speed of rejuvenation of plantations is low in Romania. Of the total area cultivated with apple trees, 70% of plantations are old, and it is obviously that production is both quantitative and qualitative low. The present study aims to analyze the apple market at the European Union level and, implicitly, at the level of Romania. To achieve this, the 2013-2017 period was was taken as the basis of study and indicators such as total production, cultivated area and average yield per hectare were taken into account. Thus, at the level of the European Union, Poland is the undisputed leader in apple production, together with Italy and France, providing about 60% of the total production recorded in the 28 countries. At the same time, the analysis also focuses on price developments in the first five apple-producing countries, and the lowest price is recorded in Poland in 2013 of only 20 cents / kg, which explains to a certain extent the presence on the Romanian market of Polish apples.
Keywords: Q13; Q17; 330; apples; apple production; producers; cultivated areas